2018
DOI: 10.1007/s00228-018-2500-y
|View full text |Cite
|
Sign up to set email alerts
|

Urgent need to modernize pharmacovigilance education in healthcare curricula: review of the literature

Abstract: ObjectivesPharmacovigilance education is essential since adverse drug reactions (ADRs) are a serious health problem and contribute to unnecessary patient burden and hospital admissions. Healthcare professionals have little awareness of pharmacovigilance and ADR reporting, and only few educational interventions had durable effects on this awareness. Our future healthcare providers should therefore acquire an adequate set of pharmacovigilance competencies to rationally prescribe, distribute, and monitor drugs. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 59 publications
4
64
0
1
Order By: Relevance
“…A recent review supported the idea that it is crucial to improve and innovate current pharmacovigilance education in undergraduate health profession students. [23] This study had few limitations. The study only focused on one nursing school and the sample size was small and hence the findings cannot be generalized to the entire nursing student population of the country.…”
Section: Discussionmentioning
confidence: 96%
“…A recent review supported the idea that it is crucial to improve and innovate current pharmacovigilance education in undergraduate health profession students. [23] This study had few limitations. The study only focused on one nursing school and the sample size was small and hence the findings cannot be generalized to the entire nursing student population of the country.…”
Section: Discussionmentioning
confidence: 96%
“…Fortunately, this obstacle can be modified by introducing more topics related to ADE reporting and drug safety within pharmacy curriculum, providing continuing education programmes and training as suggested by several studies included in this review. A recent literature review about pharmacovigilance education showed that pharmacovigilance interventions can range from short PowerPoint presentations and several training and interactive workshops . Intervention types included providing theoretical information about ADR reporting, identification of ADRs, medication safety modules, detection of ADRs and lectures on completing MedWatch forms .…”
Section: Discussionmentioning
confidence: 99%
“…[86] Intervention types included providing theoretical information about ADR reporting, identification of ADRs, medication safety modules, detection of ADRs and lectures on completing MedWatch forms. [86] Other barriers that were frequently mentioned can also be linked to lack of knowledge, such as uncertainty that a specific drug is responsible to a particular drug reaction, and ADE is too trivial and well known to report. Yet, in reality, even, suspected ADE and all possible types of undesirable effects associated with a drug can be reported.…”
Section: Self-administeredmentioning
confidence: 99%
“…The drug regulatory body needs to increase attention and focus on targeting community pharmacists and continue attempts to hold educational campaigns and workshops for all healthcare providers. [13,14] SFDA has developed a mobile application that provides the user with notification for any warnings and alerts, awareness messages regarding food, medications and medical devices in addition to a special section for pharmacovigilance in order to make the reporting process more accessible. This mobile app can ease the access to the electronic ADR form, obviating the need to go to the main page of the SFDA website and start a search within a site.…”
Section: Discussionmentioning
confidence: 99%